Civil liability for dangerous activities: Reestablishing nexus between private juridical persons and human right violations in Colombia (2012)
This research paper proposes that the Colombian Supreme Court's doctrine of liability for dangerous activities provides a useful framework to establish the nexus between juridical persons and human rights violations in the country. This article, based on an analysis of international and national law and doctrine on the subject, establishes that the absence of criminal liability of juridical persons in Colombia is a major obstacle to determining the contribution of these corporate structures to the Colombian armed conflict. This paper therefore explores other legal avenues to redress the human rights harms caused by legal persons, like liability for dangerous activities, that do not entail structural legal reforms but using existing institutions.